Longitudinal Outcomes of Women Undergoing Transcatheter Aortic Valve Replacement. Issue 4 (August 2019) - Kilic, Arman; Bianco, Valentino; Gleason, Thomas G.; Lee, Joon S.; Schindler, John; Navid, Forozan; Kliner, Dustin; Cavalcante, Joao L.; Mulukutla, Suresh R.; Sultan, Ibrahim
Objective: Recent data have suggested that women have a survival benefit at 1-year follow-up. However, long-term gender-based TAVR outcomes are lacking. Methods: All patients undergoing isolated TAVR from 2011 to 2017 were included. Patients were stratified by gender. The primary outcomes of the study were 3-year mortality and 3-year hospital readmissions. Multivariable logistic regression analysis was used to evaluate the risk-adjusted impact of gender on TAVR outcomes. Results: A total of 1, 036 patients were divided into male ( n = 518) and female ( n = 518) cohorts. Women had a borderline significantly increased STS PROM (8.3% ± 5 vs. 7.7% ± 4.4; P = 0.05). The majority of procedures were performed under conscious sedation (male: 89% vs. female: 88%; P = 0.62) and via transfemoral access (male: 81.8% vs. female: 81.4%; P = 0.46). There was no difference in operative (30-day) mortality (male: 15 [3.3%] vs. female: 17 [3.7%]; P = 0.77) or 30-day readmissions (male: 40 [10.8%] vs. female: 44 [12.2%]; P = 0.56). Perioperative blood product usage was higher for women (male: 8.1% vs. female: 14.1%; P = 0.002). There was no significant difference in major vascular complications (male: 0.4% vs. female: 1.0%; P = 0.26) or major bleeding (male: 0.2% vs. female: 0.4%; P = 0.56). Permanent pacemaker placement was higher for males (11.6% vs. 7.0%; P = 0.01). On risk-adjusted multivariable analysis, gender was not a factor associated with mortality (HR 0.99 [0.76 to 1.30]; P = 0.99) or readmission (HR 0.90 [0.72 to 1.14]; P = 0.42) at 5 years. Conclusions: There was no difference in survival or readmissions on multivariable analysis for women undergoing TAVR at 3 years. Longitudinal multi-institutional data will be important to validate these findings.